Newly formed vacuoles in root meristems of barley and pea seedlings have characteristics of both protein storage and lytic vacuoles - Olbrich, Andrea; Hillmer, Stefan; Hinz, Giselbert; Oliviusson, Peter; Robinson, David G. (Plant physiology, 2007)
Plant cells are considered to possess functionally different types of vacuoles in the same cell. One of the papers cited in support of this concept reported that protein storage and lytic vacuoles in root tips of barley (Hordeum vulgare) and pea (Pisum sativum) seedlings were initially separate compartments that later fused to form a central vacuole during cell elongation. We have reinvestigated the situation in these two roots using immunogold electron microscopy as well as immunofluorescence microscopy of histological sections. Using antisera generated against the whole protein of α-tonoplast intrinsic protein (TIP) as well as specific C-terminal TIP peptide antisera against α-, γ-, and δ-TIP, together with antisera against the storage proteins barley lectin and pea legumin and vicilin, we were unable to obtain evidence for separate vacuole populations. Instead, our observations point to the formation of a single type of vacuole in cells differentiating both proximally and distally from the root meristem. This is a hybrid-type vacuole containing storage proteins and having both α- and γ-TIPs, but not δ-TIP, in its tonoplast. As cells differentiate toward the zone of elongation, their vacuoles are characterized by increasing amounts of γ-TIP and decreasing amounts of α-TIP.